Attitudes about love and emotional dependence in university students of Tarapoto city Abstract - Vásquez Saldaña, Jazmín Mishell (2023)
Objective: determine if there is a significant relationship between attitudes about love and emotional dependence in university students from the city of Tarapoto. Methodology: non-experimental design of a simple correlational type, 306 university students participated (50.7% women) aged 18 to 46 (Me=25.00; SD=5.875) chosen through non-probabilistic snowball sampling. The Love Attitudes Scale (LAS) by Hendrick and Hendrick (1986) adapted by Lascurain et al. was applied to them. (2016) and the emotional dependence scale validated by Ventura and Caycho (2016). Results: a significant relationship (p=0.000) was demonstrated between emotional dependence and attitudes about love ludus (rho=0.405), pragma (rho=0.294), mania (rho=0.391), agape (rho=0.205) and storge (rho=0.168). Conclusion: There is a relationship between the variables studied.